Creation of exceptions to the right to life by the European Court of Human Rights on the example of case law on euthanasia and assisted suicide - Roszkiewicz, Janusz (The phenomenon of euthanasia: Philosophy – Culture – Medicine – Law, 2025)
The subject of this article is analysis of unwritten exceptions to the right to life which do not result from Article 2 (2) of the European Convention on Human Rights, but have been established by the case-law of the European Court of Human Rights. These exceptions include: 1) the patient’s right to end his life with the help of a third person; 2) the patient’s right to end his life with the help of the state; 3) the physician’s right to end the patient’s life; 4) the patient’s right to die with the help of the physician.